Volumizing Hyaluronic Acid Filler for Midface Volume Deficit: 2‐Year Results from a Pivotal Single‐Blind Randomized Controlled Study. Issue 11 (4th October 2013) - Jones, Derek; Murphy, Diane K.
Abstract : Background: Hyaluronic acid (HA) gels are commonly used to correct age‐related midface volume deficit (MVD), yet the Food and Drug Administration has not specifically approved them for this purpose. Objective: To study the safety and effectiveness of a new 20‐mg/mL HA gel (VYC‐20L) specifically formulated and optimized for mid‐face volumizing. Methods and Materials: A multicenter, single‐blind, controlled study randomized 235 subjects aged 35 to 65 with MVD to a treatment group and 47 to a no‐treatment control group. Responders were defined as subjects who achieved improvement of 1 point or more on the validated 6‐point Mid‐Face Volume Deficit Scale (MFVDS) at 6 months as rated live by two blinded independent evaluators. The primary endpoint required a 70% or greater treatment group response and a statistically significant difference ( p < .001) between the treatment and control group responder rates. Results: The primary endpoint was met, with 85.6% of the treatment group improving by 1 point or more on the MFVDS at month 6 and a statistically significant difference ( p < .001) between the treatment and control group responder rates. Subjects tolerated VYC‐20L well, with no unanticipated adverse device effects. Nearly half of subjects maintained correction for 24 months. Conclusion: VYC‐20L is safe and effective for age‐related MVD, with correction lasting up to 2 years.